Bilder schreiben Virtuose Ekphrasis in Philostrats Eikones - Baumann, Mario (Millennium-Studien / Millennium Studies, 2011)
The work Eikones (Imagines/Images) by Philostratus consists of 64 fictitious descriptions of images. Mario Baumann analyzes the aesthetic virtuosity which characterizes this text. The speaker who formulates the descriptions proves himself a master in interpreting the images. He creates a unique textual composition of images which continually surprises and challenges the reader due to its diversity. The text of Eikones takes up the tradition of literature and at the same time changes it through the creation of new combinations, always revealing the virtuosity of the author.